Product Market Competition and Economic Performance in Hungary - Gjersem, Carl (OECD Publishing, 2004)
The establishment of competitive markets has been one of the cornerstones Hungarian economic policy over the past decade, alongside a successful strategy of attracting foreign investment. Broad statistical measures show no signs of endemically weak domestic competition, though the country's relatively low productivity among domestic business likely signals some sheltering from international competition. The generally healthy level of competition is partly because competition legislation and its enforcement are of a good standard. Nevertheless, room for improvement is suggested in a number of areas. In particular, it is argued that individuals should be able to initiate legal actions directly, i.e. without having to proceed via the competition authority. And, it is suggested that sanctions against individuals in hard-core cartel cases are introduced. In examining specific sectors, this paper is critical of the pace of progress towards competition in the network industries. The rail ...
Keywords: Economics; Hungary